Rhetorical knowledge in legal practice and critical legal theory - Mootz, Francis J., III (Rhetoric, culture, and social critique., 2006)
A clear summary of contemporary rhetorical philosophy and its intersections with hermeneutics and critical theory. This book describes the significance of rhetorical knowledge for law through detailed discussions of some of the most difficult legal issues facing courts today, including affirmative action, gay rights, and assisted suicide. Francis J. Mootz responds to both extremes, those who argue that law is merely a rhetorical mask for the exercise of power and those who demonstrate an ideological faith in law's autonomy, and he breaks new ground by returning to modern classics in the.